TINDAK TUTUR DIREKTIF DALAM FILM SANG PEMIMPI KARYA ANDREA HIRATA - Prabawati, Nunung; Sinaga, Mangatur; Burhanudin, Dudung (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study titled Direktive Speech Acts in the Film of the Dreamer By Andrea Hirata. This study aims to analyze the categories and meanings of in the Film Direktive Speech Acts in the Film of the Dreamer By Andrea Hirata. This type of research is descriptive qualitative. The object of this research is directive speech acts. The data source that is the object of this research is a speech by a character in the film of the dreamer by Andrea Hirata.The film pemimpi is an Indonesian film released in 2009 which was adapted from the tetralogy of the novel laskar pelangi and directed by Riri Riza with producer Mira Lesmana. The film airs in cinemas in Indonesia starting December 17, 2009. The Dreamer movie is 120 minutes long. The Dreamer will be the opening film at the Jakarta International Film Festival (Jiffest) 2009 on December 4, 2009. The Dreamer is the second best-selling film in 2009 with a total audience of 1.9 million people. To obtain research data the author conducted a library data observation technique in the speech indicated to contain the category and meaning of directive speech acts. The data of this study amounted to 93 data. The results of this study indicate that the first category of directive speech acts in the movie The Dreamer by Andrea Hirata 1) command directive 2) request directive 3) invitation directive 4) counsel directive 5) criticism directive 6) prohibited directive 7) question 8 directive) directive permissives, the two meanings of directive speech acts in the film Sang Pemimpi by Andrea Hirata the meaning of governing, the meaning of instructing, meaning of telling, meaning of begging, meaning requiring, meaning of asking, meaning of inviting, meaning of persuading, meaning of supporting, meaning of seducing, meaning of seducing, meaning of reminding, meaning of advising , meaning directing, meaning appealing, meaning advocating, meaning suggesting, meaning of swearing, meaning of sarcasm, meaning of anger, meaning of rebuking, meaning of preventing, meaning of prohibiting, meaning of asking, and meaning of granting.Key Words: Directive Speech Action, Directive Speech Act Category,Directive Speech Act Meaning